2022
DOI: 10.3390/cells11152431
|View full text |Cite
|
Sign up to set email alerts
|

WNT Activation and TGFβ-Smad Inhibition Potentiate Stemness of Mammalian Auditory Neuroprogenitors for High-Throughput Generation of Functional Auditory Neurons In Vitro

Abstract: Hearing loss affects over 460 million people worldwide and is a major socioeconomic burden. Both genetic and environmental factors (i.e., noise overexposure, ototoxic drug treatment and ageing), promote the irreversible degeneration of cochlear hair cells and associated auditory neurons, leading to sensorineural hearing loss. In contrast to birds, fish and amphibians, the mammalian inner ear is virtually unable to regenerate due to the limited stemness of auditory progenitors, and no causal treatment is able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…Research has shown that the co-administration of WNT agonist and TGFβ/SMAD inhibitors leads to a notable enhancement in the development of existential neurospheres, as well as the potential to grow auditory neural precursors 47 and induce ONPs. 27 SGN-like cells were gradually induced and differentiated without the use of FGF3 and FGF10 by mimicking the development and differentiation of SGNs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the co-administration of WNT agonist and TGFβ/SMAD inhibitors leads to a notable enhancement in the development of existential neurospheres, as well as the potential to grow auditory neural precursors 47 and induce ONPs. 27 SGN-like cells were gradually induced and differentiated without the use of FGF3 and FGF10 by mimicking the development and differentiation of SGNs in vivo .…”
Section: Discussionmentioning
confidence: 99%